Measurement of Damping Ratios of Hollow Sandwich Slabs Under Close-Contact Blast Load - Bakir, Dursun; Savas, Sedat (Mdpi, 2026)
To prevent structural damage in a contact explosion, the blast load must be discharged without damaging the structure. Contact blast tests were conducted in our study using TNT-equivalent explosives of between 125 g and 350 g, and prefabricated hollow-core plates were utilized to evacuate the blast load. Two types of hollow sandwich plates (HSPs) were designed with reference to this experiment. Then, contact and close-contact explosions were carried out on HSP samples using between 350 g and 1100 g of TNT-equivalent explosives. Comparisons were conducted using pressure/time charts from the blast tests and numerical analyses of the smoothed particle hydrodynamics (SPH) model. As a result of the experiments, the limit blast load that the sandwich slab structure can carry while maintaining its stability during a contact blast was determined, and it was found that drainage took place on the slab at a level of 10% of the limit explosion pressure load it could carry. This mitigated the explosive energy of the hollow structure by draining it from the voids without compromising the integrity of the structure.
Keywords: contact explosion; hollow sandwich plate; blast load; blast pressure drainage